2022
DOI: 10.1111/ajt.16794
|View full text |Cite
|
Sign up to set email alerts
|

Lung transplantation after ex vivo lung perfusion versus static cold storage: An institutional cost analysis

Abstract: Ex vivo lung perfusion (EVLP) is a novel lung preservation strategy that facilitates the use of marginal allografts; however, it is more expensive than static cold storage (SCS). To understand how preservation method might affect postoperative costs, we compared outcomes and index hospitalization costs among matched EVLP and SCS preserved lung transplant (LTx) recipients at a single, high‐volume institution. A total of 22 EVLP and 66 matched SCS LTx recipients were included; SCS grafts were further stratified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The desire for daytime lung transplantation surgery is hampered by the fact that, for many medical centers, it increases costs ( 14 ). However, for our institution, which is a referral cardiothoracic center, prevention of night-time lung transplantation allows us more flexibility when arranging adequate cardiothoracic emergency care.…”
Section: Discussionmentioning
confidence: 99%
“…The desire for daytime lung transplantation surgery is hampered by the fact that, for many medical centers, it increases costs ( 14 ). However, for our institution, which is a referral cardiothoracic center, prevention of night-time lung transplantation allows us more flexibility when arranging adequate cardiothoracic emergency care.…”
Section: Discussionmentioning
confidence: 99%
“…These additional costs do not take into account the capital investment required to initiate an EVLP program, train and retain on‐call EVLP staff, and allocate operating room space if EVLP with a non‐portable circuit is being performed. While medial reimbursement for EVLP is highly variable around the country, for high‐volume centers, these costs are offset by the growth in transplant volume that EVLP offers, allowing an EVLP program to be profitable at an institution level 40 . However, for smaller transplant programs where EVLP is used infrequently, the added costs may be difficult to justify.…”
Section: Trends and Barriers To Adoptionmentioning
confidence: 99%
“…While medial reimbursement for EVLP is highly variable around the country, for highvolume centers, these costs are offset by the growth in transplant volume that EVLP offers, allowing an EVLP program to be profitable at an institution level. 40 However, for smaller transplant programs where EVLP is used infrequently, the added costs may be difficult to justify.…”
Section: Trends and Barriers To Adoptionmentioning
confidence: 99%
“…However, EVLP is costlier than cold storage. Halpern 1 and colleagues from Durham, NC, compared perioperative outcomes and index hospitalization costs from EVLP ( n = 22) and non‐EVLP ( n = 66) lung transplants in a single institution. Excluding device‐specific costs, they observed that direct variable and total index hospitalization costs were higher among EVLP patients.…”
Section: Lung Perfusion and Preservationmentioning
confidence: 99%